REQUEST EXPRESSION USED BY THE ENGLISH DEPARTMENT STUDENTS OF UNIVERSITY MUHAMMADIYAH OF BENGKULU - Desti Handayani (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2015)
In this research the researcher want to know what are the forms and what it the request strategythat frequently used by the English department students of UMB. The objectives of this researchwere to know and describe the form of request expressions used by the English departmentstudents of UMB, and also to find out the request strategy that frequently used by the firstsemester students of English Department of UMB, Academic Year 2010-2011. The design ofthis research was descriptive method. The population of this research was the first semester ofEnglish Department students of UMB. The sample was 37 students from each class. The datawere collected by using the cards, and the samples expressed the instruction based on thecards. The data were analyzed based on the category framework of request strategies proposedby Blum-Kulka et al (1989). The result of this research showed that most English departmentstudents of UMB in the first semester Academic Year 2010-2011 expressed the request by usingthe form of request such as ‘can you’, ‘could you’, would you’, and there were some studentswho add the word ‘please’, at the beginning or at the end of sentence when they expressed theirrequest. From the three categories of request strategies written by Blum-Kulka et.al (1989),Direct level, Conventionally Indirect Level, and Non-Conventionally Indirect level, thestudents only used the conventionally indirect level when they expressed the request to thehearer, there were ‘can’, ‘could’, and ‘would’ that involves in query preparatory.From theresult of this research, the researcher can conclude that there are some forms of requestexpression that used by the English Department students, such as can you, could you, andwould you. From the categories of request strategies written by Blum-Kulka et.al 1989, thestudents only used the conventionally indirect level when they expressed the request to thehearer, there are can, could, and would. Based on the result, the researcher suggest thestudents to study more about speech act especially in request expression. The researcher alsosuggest the other researcher to do further research about request expression based on thestrategy in request. The researcher also suggests the lecturers to motivate their students to usespeech act with appropriate grammar when they expressed the request in real lifecommunication.